Cyber-intimate partner violence (C-IPV) and its risk factors among women in Malaysia - Yuhaniz Ahmad; Salmi Razali (PLoS ONE, 2025)
Cyber Intimate Partner Violence (C-IPV) is a serious challenge that negatively impacts the physical, mental and social health of victims. This study aims to estimate the prevalence of C-IPV among Malaysian women and identify associated risk factors. This cross-sectional study used an online questionnaire distributed through social media. A total of 1,838 female respondents aged 18–62 years participated, with 49.6% reported experiencing C-IPV. By taking into account all variables into a multiple logistic regression model, significant risk and protective factors for C-IPV were identified. Ethnicity, occupation, income and alcohol consumption were significantly increased the odds of C-IPV, while religion, marital status and number of active partners were identified as significant protective factors. The results of the study showed a significant positive relationship between C-IPV and face-to-face intimate partner violence (F2F-IPV). These findings emphasize the need for holistic intervention strategies involving multiple parties to eliminate intimate partner cyberbullying. This study suggests improving cybersecurity policies and community education programs to increase awareness and prevention of C-IPV.